2023
DOI: 10.1038/s41598-023-30150-9
|View full text |Cite
|
Sign up to set email alerts
|

A new improved generalized class of estimators for population distribution function using auxiliary variable under simple random sampling

Abstract: This article aims to suggest a new improved generalized class of estimators for finite population distribution function of the study and the auxiliary variables as well as mean of the usual auxiliary variable under simple random sampling. The numerical expressions for the bias and mean squared error (MSE) are derived up to first degree of approximation. From our generalized class of estimators, we obtained two improved estimators. The gain in second proposed estimator is more as compared to first estimator. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The biases of and respectively are given in equation [ 16 , 17 ]: and the MSEs of and are given in equation [ 18 , 19 ]: The [9] also proposed a generalized ratio-type mean estimator, given in equation [ 20 ]: …”
Section: Existing Estimatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The biases of and respectively are given in equation [ 16 , 17 ]: and the MSEs of and are given in equation [ 18 , 19 ]: The [9] also proposed a generalized ratio-type mean estimator, given in equation [ 20 ]: …”
Section: Existing Estimatorsmentioning
confidence: 99%
“…[ [16] , [17] , [18] ], subsamples of non-respondents were taken using two-phase sampling technique, and developed several mean estimators of a finite population. In case of multi-auxiliary variables [ 19 ], suggested several estimators for population mean estimation. Under the situation of non-response.…”
Section: Introductionmentioning
confidence: 99%
“…The [ 19 ] suggested a novel estimator for population mean using idea of rank under stratified random sampling. The [ 20 ] discussed a new family of estimators using rank idea for population distribution function. Some latest works done using rank set sampling see Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Mahdizadeh and Zamanzade 11 proposed an interval estimation of the population mean in ranked set sampling. Ahmad et al 12 recommended a new improved generalized class of estimators for population distribution function using the auxiliary variable under simple random sampling. Muhammad et al 13 suggested an enhanced ratio-type estimator for finite population mean using the auxiliary variable in simple random sampling.…”
Section: Introductionmentioning
confidence: 99%